Cancer stem cells and fibroblast niche cross talk in an in‐vitro oral dysplasia model. Issue 5 (31st January 2019) - Kulsum, Safeena; Raju, Nalini; Raghavan, Nisheena; Ramanjanappa, Ravindra D. R.; Sharma, Anupam; Mehta, Alka; Kuriakose, Moni A.; Suresh, Amritha
Abstract : Understanding the cellular interactions during oral carcinogenesis has the potential to identify novel prognostic and therapeutic targets. This study aimed at investigating the cancer stem cell (CSC)‐fibroblast niche interactions using in‐vitro dysplastic cell line models developed from different stages of 4NQO‐induced oral carcinogenic mice model. The spontaneously transformed epithelial cells (DysMSCTR6, 14 and 16) were developed from three time points (mild/moderate/severe), while two fibroblast cell lines (FibroMSCTR12, 16) were developed from moderate and severe dysplastic tissue. The epithelial ( Epcam+/Ck+) and the fibroblast cell lines (Vimentin+/α‐SMA+/Ck‐) were authenticated and assessment of cells representing progressive grades of dysplastic severity indicated a significant increase in dysplastic marker profile ( P  < 0.05). Evaluation of the CSC characteristics showed that an increase in expression of Cd133, Cd44, Aldh1a1, Notch1, and Sox2 was accompanied by an increase in migratory ( P  > 0.05) and colony formation capacity ( P  > 0.005). Targeting Notch1 (GSI inhibitor PZ0187; 30 μM), showed a significant reduction in cell proliferation capacity ( P  < 0.05) and in the dysplastic marker profile. Further, Notch1 inhibition resulted in down regulation of Cd133 and Aldh1a 1 ( P  < 0.05) and a complete abrogation of colony formation ability ( P  < 0.0001). The effect of niche interactions evaluated using FibroMSCTR12‐conditioned media studies, revealed an enrichment of ALDH1A1+ cells ( P  < 0.05), induction of spheroid formation ability ( P  < 0.0001) and increased proliferation capacity (3.7 fold; P  < 0.005). Although PZ0187 reduced cell viability by ∼40%, was unable to abrogate the conditioned‐media induced increase in proliferation capacity completely. This study reports a Notch‐1 dependent enrichment of CSC properties during dysplastic progression and a Notch‐1 independent dysplastic cell‐fibroblast interaction during oral carcinogenesis.